TELAAH HUKUM MENUTUP AURAT DAN MENJAGA PANDANGAN DI ERA DIGITAL DALAM TAFSIR AYAT AL-AHKAM KARYA ASH-SHABUNI - Muhamad Rulyawan Sihab; Rifki Maulana, Yoan (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
This study examines Shaykh Muhammad Ali Ash-Shabuni’s interpretation of QS. An-Nur verses 30–31 in Tafsir Ayat al-Ahkam and its relevance to the phenomenon of Muslim women on social media who tend to neglect the ethics of lowering the gaze and covering the aurat. This research employs a qualitative approach using library research and content analysis of the tafsir text and supporting literature. The findings reveal that Ash-Shabuni emphasizes the importance of lowering the gaze and covering the aurat as acts of worship, self-protection, and obedience to Allah. In the digital era, these values remain relevant to counter the trend of bodily exposure for online visibility. This study contributes to contemporary Islamic legal discourse by highlighting the importance of internalizing modesty, dress ethics, and spiritual awareness in online interactions, particularly for Muslim women.